2022
DOI: 10.1108/maem-01-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

Green finance and high-quality development of marine economy

Abstract: PurposeWith the Chinese marine economy developing rapidly, the environmental problem has been occurring frequently, which needs green finance that supports energy conservation, environmental protection, and sustainable development to solve.Design/methodology/approachIn this paper, the entropy method is used to measure the development level of green finance, the DEA-ML index is used to measure the green total factor productivity which is used to indicate the high-quality development level of the marine economy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, while stakeholders with non‐contractual relationships to businesses have a positive impact on GIs, governmental administrations can have a detrimental effect, hindering businesses' efforts to implement GI (Srouji et al, 2023; Thomas et al, 2021). The findings, nonetheless, indicate that the level of development of the GI can support high‐quality economic performance (Alsmadi et al, 2023; Khairunnessa et al, 2021; Xu & Gao, 2022). However, the GI in Jordanian financial sector verified none of these indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while stakeholders with non‐contractual relationships to businesses have a positive impact on GIs, governmental administrations can have a detrimental effect, hindering businesses' efforts to implement GI (Srouji et al, 2023; Thomas et al, 2021). The findings, nonetheless, indicate that the level of development of the GI can support high‐quality economic performance (Alsmadi et al, 2023; Khairunnessa et al, 2021; Xu & Gao, 2022). However, the GI in Jordanian financial sector verified none of these indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Green management innovation, green process innovation, and green product innovation comprise this concept (Chen et al, 2022;Srouji et al, 2023). Financial institutions have identified green finance as a way to minimize environmental risk and promote environmental quality (Xu & Gao, 2022). As part of its corporate social responsibility, the building sector often prioritizes climate change (Soares, 2022).…”
Section: Green Innovationmentioning
confidence: 99%
“…Several previous studies have indicated that a transition to a green economy can be achieved through the following sectors (Table 6). 23 (Govindaraju et al, 2022;Weber & Cabras, 2017;Ringel et al, 2016;Knuth, 2018;He et al, 2019;Yi & Liu, 2015;Sarwar, 2022;Rathore et al, 2022;Wu et al, 2021;Solaymani, 2020;Matraeva et al, 2019;Shah & Niles, 2016;Amankwah-Amoah & Sarpong, 2016;Musango et al, 2014;Diyar et al, 2014;Papoutsoglou et al, 2022;Taskın et al, 2020;Conti et al, 2018;Pahle et al, 2016;Ürge-Vorsatz et al ,2016;Gouvea et al, 2013) Green growth 4 (Dmuchowski et al, 2021;Luukkanen et al, 2018;Dornan et al, 2018;Gainsborough ,2017) Green finance 2 (Xu & Gao, 2022;Dulal et al, 2015) Climate change adaptations 2 (Ansah & Sorooshian, 2019;Bhopal et al, 2021) Corporate social responsibility 1 (Macro-Fondevila et al, 2017) Supply chain integration 1 (Sinnandavar et al, 2018) Gender equity (women in environmental management, cultural dimensions) 3 (Nhamo & Chipo, 2020;Lee et al, 2022;Bauhardt, 2014) Training and education 2 (Lebedev et al, 2015;Rosenberg e...…”
Section: Classification By the Methods Used To Transition To Green Ec...mentioning
confidence: 99%
“…In the context of carbon peak and carbon neutrality, digital green innovation development is becoming more and more important for enterprises. In order to effectively improve green competitiveness and increase profits, photovoltaic building materials enterprises must choose digital green innovation projects for investment [23].…”
Section: Industry 50 Promotes Green Technology Innovation With Sustai...mentioning
confidence: 99%